2009
DOI: 10.1177/1350507609340809
|View full text |Cite
|
Sign up to set email alerts
|

The Silent and the Silenced in Organizational Knowing and Learning

Abstract: Research on silence within organizations and learning is sparse. This article is concerned with exploring the concept of silence in organizational settings, delineating its various forms (silent and silenced) and critically examining the relevance of these various manifestations for management and organizational learning. Following a brief review of the concept of the Polanyian notion of tacitness and how it relates to our conceptualization of silence, we offer a taxonomy of silence comprised of several ways o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 60 publications
2
53
0
5
Order By: Relevance
“…The questioning of such behaviours is required in order to further examine if and to what extent the culture of silence is impacting upon the mental and physical health/well-being of those concerned, the overall functioning of organizational efficiency, and the development of a creative workforce both within and outside of sport specific contexts. Moreover, and perhaps of greater importance, is the need for further critical investigation into the concept of 'silence', its impact upon effective organizational learning and the outcomes arising from restricting 'voice' (Blackman and Sadler-Smith 2009;Edmonson 2003;Morrison 2011), specifically within cultures that seek to adopt a holistic approach to pedagogical 33 practices. This may also elicit questions as to whether the silencing of voice impedes the transition of employees to and from organizations, making it somewhat difficult to integrate into differing working cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questioning of such behaviours is required in order to further examine if and to what extent the culture of silence is impacting upon the mental and physical health/well-being of those concerned, the overall functioning of organizational efficiency, and the development of a creative workforce both within and outside of sport specific contexts. Moreover, and perhaps of greater importance, is the need for further critical investigation into the concept of 'silence', its impact upon effective organizational learning and the outcomes arising from restricting 'voice' (Blackman and Sadler-Smith 2009;Edmonson 2003;Morrison 2011), specifically within cultures that seek to adopt a holistic approach to pedagogical 33 practices. This may also elicit questions as to whether the silencing of voice impedes the transition of employees to and from organizations, making it somewhat difficult to integrate into differing working cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In this instance, the culture of silence may be justified by, and reinforced through, an adherence to core values and a universal acceptance of key organizational rules and regulations (Argyris 1977). Further research examining specific cultural features of organizational settings has identified individualistic and competitive cultures as sites that may foster a mode of 'voluntary imposed silence' amongst employees, whereby the restriction of voice and the withholding of knowledge might be implemented as a strategy to regain control from those in positions of authority (Blackman and Sadler-Smith 2009;Pinder and Harlos 2001).…”
Section: Introductionmentioning
confidence: 99%
“…as well as patterns which themselves may be subject to differing interpretations (for example use of silence for indicating opposition or agreement) (Blackman & Sadler-Smith, 2009;SavilleTroike, 2003).…”
Section: Norms: Rules Of Interaction and Interpretationmentioning
confidence: 99%
“…This paper draws mainly from Mead and Bower (2000), who explain patient-centeredness in terms of five dimensions, and Blackman and Sadler-Smith (2009), who provide a framework explaining the concept of 'voice' and offer a taxonomy of different dimensions of silence. The paper brings together these frameworks to conceptualise patient-centred care and its components and how the patient's voice is relevant in patient-centeredness.…”
Section: Theoretical Frameworkmentioning
confidence: 99%